Forests and human health: assessing the evidence - Colfer, C.J.P.; Sheil, Douglas; Kishi, M. (Center for International Forestry Research, 2006)
This study has two central concerns: the state of human health in forests, and the causal links between forests and human health. Within this framework, we consider four issues related to tropical forests and human health. First, we discuss forest foods, emphasizing the forest as a food-producing habitat, human dependence on forest foods, the nutritional contributions of such foods, and nutrition-related problems that affect forest peoples. Our second topic is disease and other health problems. In addition to the major problems—HIV/AIDS, malaria, Ebola and mercury poisoning—we address some 20 other tropical diseases and health problems related to forests. The third topic is medicinal products. We review the biophysical properties of medicinal species and consider related indigenous knowledge, human uses of medicinal forest products, the serious threats to forest sustainability, and the roles of traditional healers, with a discussion of the benefits of forest medicines and conflicts over their distribution. Our fourth and final topic is the cultural interpretations of human health found among forest peoples, including holistic world views that impinge on health and indigenous knowledge. The Occasional Paper concludes with some observations about the current state of our knowledge, its utility and shortcomings, and our suggestions for future research.